Raw materials in the foreign trade of the LDCs - Dietrich Kebschull (Intereconomics, 1975)
The developing countries' championship of what they term an “integrated approach for raw materials” is one of the livellest subjects in the Federal Republic of Germany. Bonn suggests a pragmatic, as distinct from an ideological, approach — for the benefit of the Third World. For this reason it has to be analyzed, whether the raw material sector is the ideal basis for the improvement of the existing situation.
Keywords: 330; Foreign Trade